2017
DOI: 10.1007/s11126-016-9486-3
|View full text |Cite
|
Sign up to set email alerts
|

Everything in Moderation: Moderate Use of Screens Unassociated with Child Behavior Problems

Abstract: The impact of children's use of "screen" media including television and computer games, continues to be debated. The American Academy of Pediatrics (AAP) until recently recommended a relatively restrictive screen time diet of 2 h or less for most youth. A representative correlational sample of youth were assessed for links between screen time and risky behavioral outcomes. Data collection occurred in 2013 conducted by the State of Florida. Use of screens that was moderately high, in excess of the AAP's former … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 11 publications
4
58
0
2
Order By: Relevance
“…Additional analyses indicated linear and parabolic relations linking daily digital screen time and some indicators of psychological well‐being. These findings conceptually replicated results reported from studies with older children, showing there may be some benefits of screen use (Ferguson, ; Przybylski & Weinstein, ). They suggested that there might be extremely small positive effects of digital engagement at levels higher than what many might assume (up to 7 hr/day for both television and computer‐based media).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Additional analyses indicated linear and parabolic relations linking daily digital screen time and some indicators of psychological well‐being. These findings conceptually replicated results reported from studies with older children, showing there may be some benefits of screen use (Ferguson, ; Przybylski & Weinstein, ). They suggested that there might be extremely small positive effects of digital engagement at levels higher than what many might assume (up to 7 hr/day for both television and computer‐based media).…”
Section: Discussionsupporting
confidence: 82%
“…*Because eight statistical tests evaluated, the threshold for statistical significance has been adjusted to p < .00625 to account for the family-wise error rate associated with conducting eight tests. may be some benefits of screen use (Ferguson, 2017;Przybylski & Weinstein, 2017). They suggested that there might be extremely small positive effects of digital engagement at levels higher than what many might assume (up to 7 hr/day for both television and computer-based media).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recently published comprehensive and systematic review reported evidence for an association between higher levels of screen consumption (including gaming) and unfavorable body composition and/or fitness (Carson et al 2016). While most of the relevant scientific literature supports the position that time allocated to screen-based activities should be in harmony with other activities that are considered more advantageous, there is no consensus about its importance in relation to risky behavior outcomes (Carson et al 2016;Ferguson 2017), further indicating that quality matters of behavior may imply more.…”
mentioning
confidence: 99%
“…Whereas the foregoing studies have documented negative associations between screen time and well‐being, other studies have found no effects, mixed effects, or opposite effects (Ferguson, 2017; Przybylski & Weinstein, 2018). Programming that is age and developmentally appropriate for preschoolers, such as Daniel Tiger's Neighborhood or Sesame Street can have beneficial effects.…”
Section: Growing Concern Over Excessive Recreational Screen Timementioning
confidence: 90%